2015
DOI: 10.5001/omj.2015.88
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Coherence as a Predictor of Quality of Life Among Iranian Students Living in Ahvaz

Abstract: This study shows that SOC and marital status are significant predictors of QOL among Iranian students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…2 Henning et al found a correlation between being married and lower psychological distress during medical training, 14 and Lloyd and Musser discovered in a cross-sectional study that married male students had the lowest reported total mean stress score while never married females had the highest stress scores. This optimistic finding was somewhat surprising since previous research had found an increase of stress levels and their detrimental effects across the dental school years.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…2 Henning et al found a correlation between being married and lower psychological distress during medical training, 14 and Lloyd and Musser discovered in a cross-sectional study that married male students had the lowest reported total mean stress score while never married females had the highest stress scores. This optimistic finding was somewhat surprising since previous research had found an increase of stress levels and their detrimental effects across the dental school years.…”
Section: Resultsmentioning
confidence: 97%
“…A steady source of support from a spouse or significant other has been previously associated with higher psychological health, social relationships, and environmental health. 2 Henning et al found a correlation between being married and lower psychological distress during medical training, 14 and Lloyd and Musser discovered in a cross-sectional study that married male students had the lowest reported total mean stress score while never married females had the highest stress scores. 27 Older dental students were found in our study to have lower quality of life in the Physical Health domain.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations